Breast cancer in Wilms tumor survivors: New insights into primary and secondary prevention. Issue 23 (27th October 2014) - Dean, Jennifer B.; Dome, Jeffrey S.
Abstract : Pediatric oncology providers should closely evaluate their female survivors of Wilms tumor for risk factors for the development of breast cancer, including chest radiography (even at doses <20 gray), age >10 years at the time of Wilms tumor diagnosis, and, possibly, radiotherapy to the flank. Those patients deemed to be at high risk should undergo breast cancer surveillance with mammography, breast magnetic resonance imaging, or both starting at age 25 years.